2021
DOI: 10.1038/s41598-021-81374-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram lead selection for intelligent screening of patients with systolic heart failure

Abstract: Electrocardiogram (ECG)-based intelligent screening for systolic heart failure (HF) is an emerging method that could become a low-cost and rapid screening tool for early diagnosis of the disease before the comprehensive echocardiographic procedure. We collected 12-lead ECG signals from 900 systolic HF patients (ejection fraction, EF < 50%) and 900 individuals with normal EF in the absence of HF symptoms. The 12-lead ECG signals were converted by continuous wavelet transform (CWT) to 2D spectra and classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Studies show excellent performance metrics with these (Table 3). [21][22][23][24][25][26][27][28][29][30][31][32][33][34] By detecting subtle changes in cardiac structure and function over time, ML algorithms can assist in identifying early indicators of HF. This early detection can facilitate timely interventions and preventative measures, thereby potentially reducing the burden of HF and enhancing patient outcomes.…”
Section: Heart Failure Diagnosismentioning
confidence: 99%
“…Studies show excellent performance metrics with these (Table 3). [21][22][23][24][25][26][27][28][29][30][31][32][33][34] By detecting subtle changes in cardiac structure and function over time, ML algorithms can assist in identifying early indicators of HF. This early detection can facilitate timely interventions and preventative measures, thereby potentially reducing the burden of HF and enhancing patient outcomes.…”
Section: Heart Failure Diagnosismentioning
confidence: 99%
“…In a recent explosion in popularity, NNs are being widely used in cardiac EP, from predicting AF or congestive heart failure from heart rate variability biomarkers, to predicting the presence of acute myocardial infarction from an ECG. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] NN models have been preferred in these studies because they can practically operate on any data type, and they inherently learn feature importance and the relationships between features. These studies have demonstrated the advantages of NN in handling raw ECG data, raw LGE-MRI signals, electroanatomic mapping (EAM) data, and overall, in learning from high dimensional complex data.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Following a pre-processing procedure, the signals were transformed into a bidimensional spectrum using continuous wavelet transform [46] for presentation to the deep learning system, developed to discriminate 31 and later 30 different ECG and RRI classes as responses to different types of HMI and noise. The system used the ResNet-18 [47] and GoogLeNet [48] pre-trained convolutional neural networks; deep learning allows for dealing with several dependencies at once, such as all classes of stimuli in the study.…”
Section: Introductionmentioning
confidence: 99%